Water Stagnation and Flow Obstruction Reduces the Quality of Potable Water and Increases the Risk of Legionelloses - Nisar, Muhammad Atif; Ross, Kirstin E.; Brown, Melissa H.; Bentham, Richard; Whiley, Harriet (Frontiers in Environmental Science, 2020)
Legionella is an opportunistic waterborne pathogen associated with Legionnaires' disease and Pontiac fever. Despite improved public awareness, the incidence of Legionella associated infections has been increasing. Aerosols generated from engineered potable water systems are a demonstrated cause of both nosocomial and community-acquired legionellosis. The ecology of Legionella in these systems is complex with multiple factors impacting their colonization and persistence. Flow dynamics has been identified as an important factor and stagnation in cooling towers is an accepted risk for increased Legionella growth; however, less is known about the impact of flow dynamic on Legionella in potable water systems. This is especially complex due to the inherent intermittent and variable usage observed within outlets of a potable water system. This systematic literature review examines the role of fluid dynamics and stagnation on the colonization and growth of Legionella in potable water systems. Twenty two of 24 identified studies show a positive association between stagnation zones and increased colonization of Legionella. These zones included dead legs, dead ends, storage tanks and obstructed water flow (such as intermittent usage or flow restriction). Prolonged stagnation in building plumbing systems also deteriorates the quality of thermally or chemically treated potable water. This stimulates the colonisation of Legionella established biofilms. Such biofilms are intrinsically resistant to disinfection procedures and accelerate the rate of decay of chemical disinfectants. Sub-lethal doses of disinfectants and the presence of protozoan hosts in stationary water promote generation of viable but non-culturable Legionella cells. This results in false negatives in surveillance methods that use culture methodology. In conclusion, elimination of temporal and permanent stagnation points can improve the quality of potable water, efficacy of disinfectants and reduce the risk of legionellosis. Current guidelines and water safety plans recognise the risks associated with permanent stagnation point (dead ends and dead legs); however, there is a need for greater emphasis on controlling temporal stagnation arising from intermittent usage.